2019
DOI: 10.3233/jad-190757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chlorogenic Acids on Cognitive Function in Mild Cognitive Impairment: A Randomized Controlled Crossover Trial

Abstract: Background: Mild cognitive impairment (MCI) is a global-scale issue, due in large part to the rapidly growing elderly population. The main polyphenol contained in coffee beans, chlorogenic acid (CGA), improves attention in healthy individuals. The utility of CGAs for treating MCI, however, has not been evaluated. Objective: To determine the effects of continuous CGA intake on cognitive function, especially attention, in patients diagnosed with MCI. Methods: The study was a randomized controlled crossover trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 33 publications
(39 reference statements)
1
28
0
Order By: Relevance
“…A 10-year follow-up study by Larsson et al (2011) suggests that no or low coffee consumption correlates with increased risk for stroke in women (Larsson et al, 2011). Moreover, a recent randomized controlled crossover trial, which investigated the protective effects of 5-CQA against mild cognitive impairment (MCI), demonstrated the improvement of cognitive functions (executive and attention function) in patients with MCI (Ochiai, Saitou, Suzukamo, Osaki, & Asada, 2019).…”
Section: Neuroprotectionmentioning
confidence: 99%
“…A 10-year follow-up study by Larsson et al (2011) suggests that no or low coffee consumption correlates with increased risk for stroke in women (Larsson et al, 2011). Moreover, a recent randomized controlled crossover trial, which investigated the protective effects of 5-CQA against mild cognitive impairment (MCI), demonstrated the improvement of cognitive functions (executive and attention function) in patients with MCI (Ochiai, Saitou, Suzukamo, Osaki, & Asada, 2019).…”
Section: Neuroprotectionmentioning
confidence: 99%
“…Importantly, coffee has a diversity of other bioactive constituents apart from caffeine, amongst which stem chlorogenic acids 21 . As most polyphenols, chlorogenic acids have been described as potent antioxidants 22 and several studies have shown an ability of chlorogenic acids to affect brain function 23 27 . Thus, interventions with diets enriched in chlorogenic acids ameliorate mood 22 , 23 and cognitive function 25 , 26 in volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both pure chlorogenic acid and the decaffeinated green coffee blend significantly improved symptoms of headache [ 328 ]. Despite the lack of significant pro-cognitive effects after single administration [ 327 , 328 ], chlorogenic acid was reported to increase cognitive function following regular prolonged intake [ 329 , 330 ]. Saitou et al [ 330 ] investigated the effects of a 16-week intake of chlorogenic acid-added beverage or placebo on cognitive functions in 38 healthy volunteers (aged 50–69 years) with subjective memory complaints.…”
Section: Neuroprotective Effects Of Coffee Bioactive Compoundsmentioning
confidence: 99%
“…Moreover, biochemical studies revealed decreased plasma Aβ 42 and Aβ 42 /Aβ 40 levels and elevated dehydroepiandrosterone sulfate level [ 331 ]. In a recent randomized controlled crossover trial, the effect of prolonged chlorogenic acids intake on cognitive function in mild cognitive impairment was investigated [ 329 ]. The study was performed on 34 individuals and comprised two 12-week chlorogenic acids intake periods (553.6 mg of chlorogenic acids or placebo twice daily) with a 4-week washout period between them.…”
Section: Neuroprotective Effects Of Coffee Bioactive Compoundsmentioning
confidence: 99%
See 1 more Smart Citation